PENGARUH NON INTEREST INCOME, GROWTH OF ASSET, LOAN TO ASSET, CAR, DAN LOAN LOSS PROVISION TO ASSET TERHADAP RISIKO BANK - Putra, Ardhilo; Mawardi, Wisnu (Diponegoro Journal of Management, 2017)
The increasing demands of financial services and technology has led the bank to increase their service to compete in the banking industry. Other service that bank provide by now will increase non interest income and led to bank income diversification. This research was conducted to examine the effect of bank income diversification (non interest income), Growth of assets (Î”TA), Loan to asset, CAR, and Loan loss provision to asset towards bank risk measured by SDROA (Deviation Standard of Return on Asset) and SDROE (Deviation Standard of Return on Equity). We use commercial banks that listed on Indonesia Stock Exchange (IDX) through period 2011-2015 as a sample of the research and based on purposive sampling, we selected 24 banks as the sample of this research. We use multiple regression analysis to examine the effect.The Result indicate that some determinants of Bank Risk such as NNII, Loan to Asset, and Loan Loss Provision to Asset affect SDROA (Standard Deviation of Return on Asset) as a risk measure, and NNII, Î”TA, and Loan Loss Provision to Asset affect SDROE (Standard Deviation of Return on Equity) as other risk measure.Â  However, Capital Adequacy Ratio do not affect bank risk that measured by SDROA and SDROE in this research by another variables which not include in these research model.